2015
DOI: 10.1111/cid.12354
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Immunohistochemical Expression of Bone Morphogenetic Protein‐4 in Bone Maturation after Maxillary Sinus Grafting in Humans

Abstract: Our findings suggest that the native expression of BMP-4 appears to be associated with normal bone homeostasis and reparation in grafted and nongrafted maxillary sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…This result is in concordance with a previous in vivo study that investigated bone formation with BMP-2 in the rabbit maxillary sinus during the early healing period [1]. Furthermore, a recent clinical trial showed a significantly higher amount of mineralized bone formation in the higher expression of the BMP-4 group after maxillary sinus augmentation [8], which indicates that faster and greater bone formation would be induced by the BMPs.…”
Section: Discussionsupporting
confidence: 91%
“…This result is in concordance with a previous in vivo study that investigated bone formation with BMP-2 in the rabbit maxillary sinus during the early healing period [1]. Furthermore, a recent clinical trial showed a significantly higher amount of mineralized bone formation in the higher expression of the BMP-4 group after maxillary sinus augmentation [8], which indicates that faster and greater bone formation would be induced by the BMPs.…”
Section: Discussionsupporting
confidence: 91%
“…The aim of maxillary sinus augmentation is to restore the ideal bone height, enabling dental implant placement 1 . Some studies have proposed the use of bone substitutes to contribute to the maintenance of bone volume and new bone formation in the maxillary sinus [2][3][4][5][6][7] . The autogenous bone graft is still the most predictable and favourable for bone grafting because of its osteogenic, osteoinductive, and osteoconductive properties 8,9 .…”
mentioning
confidence: 99%
“…54 Bone morphogenetic protein (BMP)-4 has been shown to induce osteogenic differentiation of osteoblasts from osteoprogenitor cells. 55 Interaction of BMP-2, BMP-4, and BMP-7 may contribute to osteoinduction. 51…”
Section: Discussionmentioning
confidence: 99%
“…53 The osteoclasts follow Haversian canals, resorbing allograft bone and releasing embedded bone morphogenetic protein and growth factors, and then change to osteoblasts and eventually to osteocytes. 35,55,59–65 The process of new bone formation and remodeling initiated by osteoclastic resorption has been called reverse creeping substitution. 57…”
Section: Discussionmentioning
confidence: 99%